2016
DOI: 10.1016/j.mmcr.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium apiospermum infections and the role of combination antifungal therapy and GM-CSF: A case report and review of the literature

Abstract: Scedosporium apiospermum, a ubiquitous environmental mold, is increasingly reported as causing invasive fungal disease in immunocompromised hosts. It poses a therapeutic challenge due to its intrinsic resistance to traditional antifungals and ability to recur despite demonstrating susceptibility. We present an immunocompromised patient with a cutaneous S. apiospermum infection that disseminated despite treatment with voriconazole, the drug of choice. Adding echinocandins and GM-CSF provided partial recovery, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…A 2007 retrospective review of 107 patients with S. apiospermum and L. prolificans infection from the Pfizer VRC global clinical trials database treated with VRC as primary or salvage therapy showed overall successful therapy in 57%, with success rate varying widely by sites of infection; central nervous system infections and disseminated infections had a 43% and 48% response rate, respectively, whereas skin and subcutaneous infections had a 91% response rate . Combination therapy with VRC plus terbinafine or micafungin for synergy has also been used based on in vitro data suggesting 20‐60‐fold decrease in MIC, and at least a few successful case reports …”
Section: Discussionmentioning
confidence: 99%
“…A 2007 retrospective review of 107 patients with S. apiospermum and L. prolificans infection from the Pfizer VRC global clinical trials database treated with VRC as primary or salvage therapy showed overall successful therapy in 57%, with success rate varying widely by sites of infection; central nervous system infections and disseminated infections had a 43% and 48% response rate, respectively, whereas skin and subcutaneous infections had a 91% response rate . Combination therapy with VRC plus terbinafine or micafungin for synergy has also been used based on in vitro data suggesting 20‐60‐fold decrease in MIC, and at least a few successful case reports …”
Section: Discussionmentioning
confidence: 99%
“…Combination of micafungin and voriconazole has demonstrated a synergistic effect against several fungi in vitro including Scedosporium spp. The synergistic mechanism may include reorganization of the cell wall allowing increased exposure of beta-glucan to the immune system [44]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to antifungal agents, GM-CSF has been studied with some success [44, 45]. While antifungal therapy remains crucial to recovery, the treatment of scedosporiosis infections depends on the function of the host's innate immune system, in particular, polymorphonuclear cells (PMNs).…”
Section: Discussionmentioning
confidence: 99%
“…One alternative treatment strategy for fungal diseases aims to manipulate the host immune system to better combat infection. This includes cell‐based therapies focused on replenishing immune cells and the use of cytokines as adjunctive antifungal therapy, which has shown promising results for the treatment of invasive fungal infections in organ transplant patients, for HIV/AIDS‐associated Cryptococcus infections, and for highly drug‐resistant Scedosporium infection . Additionally, there is growing interest in the use of monoclonal antibodies to target fungal pathogens or for use in radioimmunotherapy .…”
Section: Future Prospects For Emerging Fungal Disease: Diagnosis and mentioning
confidence: 99%
“…This includes cell-based therapies focused on replenishing immune cells 266,267 and the use of cytokines as adjunctive antifungal therapy, [268][269][270][271][272] which has shown promising results for the treatment of invasive fungal infections in organ transplant patients, 271 for HIV/AIDS-associated Cryptococcus infections, 268,272 and for highly drug-resistant Scedosporium infection. 273 Additionally, there is growing interest in the use of monoclonal antibodies to target fungal pathogens 238,[274][275][276][277][278] or for use in radioimmunotherapy. 279 Other innovative approaches to immune-based antifungal therapy include a bioengineering strategy to genetically modify T cells to redirect their specificity toward Aspergillus, 280 and a targeted kinase approach in mammalian cells that negatively regulates the host antifungal immune response in order to boost innate immunity against fungal infection.…”
Section: New Alternatives For Antifungal Drug Therapymentioning
confidence: 99%